A Review on Hybrid Processes for Palm Oil Mill Effluent: Possible Approaches - Al-Amshawee, Sajjad; Mohd Yusri, Mohd Yunus; A. A., Azoddein (IOP Publishing, 2020)
The aim of this review paper is to explore and examine hybrid processes and systems for polishing palm oil mill effluent (POME). Nitrification process, and nutrients removal are highly significant to process highly contaminated POME. Besides, quality of POME process is extremely important to solve fresh water shortage that has blocked millions of people from accessing a clean water. Hence, attentions have been made on water pollution to raise a global demand to improve POME processing and discharge unharmful effluent to the waterways. For decades, using a stand-alone technology to treat POME has faced fouling, and disability to deliver the promising quality. A new approach is termed as hybrid or combined system has the ability to deliver higher performance and more effective contamination removal than stand-alone technologies. Hybrid system is a novel technique can be used to achieve higher efficacy that single physical, chemical, or biological technology can't accomplish. This review reports various hybrid systems and united technologies to treat POME including their advantages, disadvantages, and limitations.